POSITIVE EXISTENTIALISM OF ENZO PACI - Alla V. Skatershchikova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article deals with analysis of philosophic views of one representative of Italian existentialism - Enzo Pachi. It investigates principle ideas of his philosophy, his attempts to link irrational with rational in the problem of world structure. Using key sources of the essence of positive existentialism we can see how philosophy of Pachi is connected with Gusserl phenomenology, some ideas of Marx and other philosophers who thought about the human being. Positive existentialism of Pachi is considered to be non-system philosophy, which is open to different ideas and directed to uniting people through overcoming their problems. The author comes to the conclusion that philosophy of E.Pachi is an integral and important part of existentialism as a philosophic trend in general.